PENERAPAN METODE BACKPROPAGATION UNTUK MEMPREDIKSI JUMLAH KUNJUNGAN WISATAWAN BERDASARKAN TINGKAT HUNIAN HOTEL - Romy Aulia (STMIK Royal, 2018)
Tourism is one of the most important factors for the revenue of an area. To attract the interest of tourists takes some supporting factors, one of which is the hotel or the guesthouse. In the process of prediction of tourists visit, required data the number of tourists staying in order to predict for the next time. The prediction method used in this system is a method of Backpropagation Neural Network based on time series data forecasting component variansi random or random process beginning with autocorrelation for determination of input variables. Method of Backpropagation itself is known quite well used in the forecasting of time series data. The result of the method of Backpropagation is a number of predictions that tourists visit can be a reference for related officials in taking decisions for the period ahead.